Failure Analysis in High Pressure Feed Water Heaters and Method to Find the Defect in Tubes - Ramesh, M.; Manavalan, S. (International Journal of Psychosocial Rehabilitation, 2019)
The aim of this study is to analyze the causes of tube failure of the high-pressure feed water heaters in thermal power plants and to find out the defective tubes in high-pressure feed water heaters using a simple and economical method. A feed water heater is used to preheat the boiler feed water in a thermal power plant. Most of the feed water heaters used in thermal power plants are shell and tube types. In this type of feed water heater, water flows inside the tube and steam condenses outside of the tube, i.e., shell side. The source of heat used in a high-pressure feed water heater is steam bleed from the turbine. The high-pressure feed water heaters are used to improve the thermodynamic efficiency of the cycle and also reduce the coal consumption of the thermal power plant. Samples of the failure tube were taken to analyze the causes of tube failure in high-pressure feed water heaters by visual inspection, using tube thickness measurement analysis, examining the mechanical properties and chemical composition of the tube material, and methodologies for finding the tube failure in advance to prevent the breakdown of high-pressure feed water heaters. Based on the above analyses, it is observed that the high-pressure feed water heater tubes failure occurred due to tube outer diameter erosion